The Influence of Lifestyle and Self-Control on the Consumptive Behavior of Islamic Boarding School Students in Madura with Religiosity as a Mediating Variable - Zainul Arifin; Dzikrulloh Dzikrulloh; Nasrulloh Nasrulloh (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Consumptive behavior among students in Madura has become an interesting phenomenon because it emerges within a pesantren environment that strongly emphasizes simplicity and religiosity. On the other hand, the development of modern lifestyles also influences students' consumption patterns, leading to increasingly consumptive tendencies. This study aims to analyze the influence of lifestyle and self-control on consumptive behavior and examine the mediating role of religiosity. This research employed a quantitative approach with a causal associative design. Data were collected through an online questionnaire using a Likert scale distributed to 96 student-santri in Madura selected through purposive sampling based on the Lemeshow formula. Data analysis was conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM) through SmartPLS 4. The results indicate that all constructs met the validity and reliability criteria, with Cronbach's Alpha and Composite Reliability values exceeding 0.70 and Average Variance Extracted (AVE) values above 0.50. The R² values showed that consumptive behavior was explained by 71.7%, while religiosity was explained by 86.2%. The findings reveal that lifestyle does not directly affect consumptive behavior but significantly influences religiosity. Self-control significantly influences consumptive behavior but does not significantly influence religiosity. Religiosity significantly affects consumptive behavior and is proven to act as a full mediator. These findings contribute to the development of Islamic consumer psychology literature and provide practical implications for pesantren institutions in designing preventive strategies against consumptive behavior among student-santri.